Clinical Characteristics, Surgical Management and Adjuvant Therapy of Patients with Uterine Carcinosarcoma: A Retrospective Case Series - Wallwiener, C.; Hartkopf, A.; Kommoss, S.; Joachim, C.; Wallwiener, M.; Taran, F. A.; Brucker, S. (Geburtshilfe und Frauenheilkunde, 2016)
Purpose: To review a single-center experience over a 27-year period of managing uterine carcinosarcoma (UCS), focusing on surgical practice, adjuvant therapy and clinical outcome. Material and Methods: This was a retrospective study of women with histologically proven UCS treated at the Department of Obstetrics and Gynecology, University of Tübingen, Germany, between 1983 and 2010. Inpatient and outpatient records were reviewed; follow-up and survival data were ascertained. Results: The study population comprised 18 patients with UCS. Primary surgical treatment consisted of total abdominal hysterectomy in 12 patients (67 %) and laparoscopic total hysterectomy in 4 patients (22 %). Bilateral salpingo-oophorectomy was performed in 94 % of patients (17/18). Lymph nodes were evaluated in 15 patients (83 %). Positive pelvic lymph nodes were present in 2 patients (11 %). A total of 17 patients (94 %) received adjuvant therapy. Disease recurred in 7 (39 %) patients of our study group, with no recurrence noted in the 4 patients who underwent laparoscopic surgical staging. Median disease-free survival (DFS) was 48.7 months (95 % CI: 0.0–157.3) and median overall survival (OS) was 49.9 months (95 % CI: 0.0–108.2). The 5-year survival rate was 40 %. Conclusion: UCS is a rare and aggressive uterine neoplasm with high recurrence rates and metastatic potential. Surgical staging consisting of total hysterectomy with bilateral salpingo-oophorectomy and systematic lymphadenectomy is the most important treatment for patients with UCS. Adjuvant radiation therapy appears to decrease pelvic recurrence, but there is a high incidence of distant recurrence, indicating the need for additional systemic treatment.
Keywords: uterine carcinosarcoma; uterine neoplasms; surgical staging; adjuvant therapy